Freeze‐dried plasma: From damage control resuscitation to coronavirus disease 2019 therapy. Issue 7 (10th June 2022) - Peng, Henry T.; Rhind, Shawn G.; Moes, Katy; Devine, Dana; Jenkins, Craig; Beckett, Andrew
Abstract: Background: Freeze‐dried plasma (FDP) is a promising blood component for prehospital resuscitation given its logistic advantages over fresh frozen plasma (FFP). COVID‐19 convalescent (CC) plasma has been used to treat coronavirus disease 2019 (COVID‐19) patients, and its corresponding FDP has potential use during future pandemics. Therefore, we conducted the study to determine if the hemostatic and immunological properties of plasma can be retained after lyophilization. Study design and methods: Hemostatic tests were conducted with Rotational Thromboelastometry (ROTEM) and a Stago analyzer. Anti‐severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) IgG (Immunoglobulin G) and neutralizing activity were analyzed using Meso Scale Diagnostics immunoassay kits. Results: There were no differences in ROTEM parameters and Stago measurements for prothrombin time (PT), partial thromboplastin time (PTT), fibrinogen and D‐dimer concentrations, and antithrombin, factor V, VIII, and protein S activities between FFP and FDP for either pre‐COVID‐19 or CC samples. Differences were observed in INTEM clotting time and PT and PTT when comparing reconstituted FDP stored at 4°C for 24 h or room temperature for 4 h to healthy control. Both CC‐FFP and CC‐FDP showed two orders of magnitude higher concentrations of IgG antibodies against SARS‐CoV‐2 antigens than pre‐COVID‐19‐FFP and pre‐COVID‐19‐FDP and healthy control. Similarly, the CC samples showed approximately 4‐fold higher %‐inhibition of receptor binding than the pre‐COVID‐19 samples. There were no differences in either the antibody levels or neutralization activity between CC‐FFP and CC‐FDP. Discussion: We demonstrated that FDP and CC‐FDP retained the same hemostatic and antibody functional activities relative to their initial plasma sources, supporting clinical evaluation of their benefits in severe trauma and COVID‐19 patients.